Divergência genética de acessos e avaliação microbiologica e de qualidade de polpa e frutos de mangabeira - Ferreira, Edivaldo Galdino (Universidade Federal Rural do Semi-Árido, 2013)
This research had as objectives to study the genetic divergence of accessions of mangaba tree from three northeastern states, and from one midwest state of Brazil, and to observe the physicochemical and microbiological characteristics of fruits and pulps of mangaba harvested and processed With and Without Good Field Practices and With and Without Good Manufacturing Practices. Materials were collected, identified and transported to the Laboratory of Molecular Biology of the UFERSA, where, after using the right methodology and appropriate technique for extraction of DNA of genotypes, the molecular characterization of accessions of mangaba trees from three northeastern states ( PB , RN and PE ) and from one midwest state ( Mato Grosso ) was carried out . The results were analyzed in specific computer program, which also used cluster analysis (UPGMA) dendrogram in forming a chart that shows the genetic dissimilarities among genotypes. It was observed that the genotype originated from Mato Grosso had the highest coefficient of dissimilarity among the others, while the smallest dissimilarity was found between two genotypes from Paraíba. The experiment aiming to observe the physical, chemical and microbiological qualities of pulp and fruit of mangaba, using the Good Field Practices and Good Manufacturing Practices was performed at the Laboratory of Postharvest UFPB / CCA , where, with appropriate methodology, it was found great efficiency and effectiveness of the good field practices used (GFP), as well as the need to adopt and regulate this system in order to yield a better food quality, and, thereby ensuring the food security of the population . It also appears that, besides the need for adoption of the system, there is an urgent need for dissemination and awareness programs, so that they can also be tools in improving public health
Genetic divergence of accessions and microbiological and quality evaluation of pulp and fruit of mangaba tree
Keywords: Mangaba; Boas práticas; Molecular; Mangaba; Good field practices; Molecular; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA